Influence of Benzotriazole on Corrosion Inhibition of Mild Steel in Citric Acid Medium. Issue 3 (2010) - Matheswaran, P.; Ramasamy, A. K.
Abstract : Benzotriazole an organic compounds has been studied as corrosion inhibition for mild steel in 1 N citric acid by weight loss method. The result showed that the corrosion inhibition efficiency of the compound was found to be varying with the temperature and acid concentration. Also it was found that the corrosion inhibition behaviour of benzotriazole is better when the concentration of inhibitor is increased. The kinetic treatment of the results shows first order kinetics.